2013
DOI: 10.5056/jnm.2013.19.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Treatment Outcomes of 3 Subtypes of Achalasia According to the Chicago Classification in a Tertiary Institute in Korea

Abstract: Background/AimsAchalasia is classified into 3 types according to the Chicago classification. The aim of this study was to investigate characteristics and treatment outcomes of 3 achalasia subtypes in Korean patients.MethodsFifty-five patients diagnosed with achalasia based on conventional or high-resolution esophageal manometry were consecutively enrolled. Their clinical characteristics, manometric, endoscopic and esophagographic findings and treatment responses were analyzed among the 3 subtypes of achalasia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 25 publications
(36 reference statements)
9
51
1
2
Order By: Relevance
“…[4][5][6] The neural control of gastrointestinal function, including esophageal motility is related to enteric neurons. 7,8 It has been shown that changes in esophageal physiology is associated with loss of esophageal myenteric plexus neurons, which are part of the enteric nervous system (ENS) and lie within the smooth muscle layers of the esophageal wall in the aged population. [9][10][11] In addition, underlying disease (such as diabetes mellitus) conditions which is more prevalent in aged people could cause decrease of esophageal motility.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The neural control of gastrointestinal function, including esophageal motility is related to enteric neurons. 7,8 It has been shown that changes in esophageal physiology is associated with loss of esophageal myenteric plexus neurons, which are part of the enteric nervous system (ENS) and lie within the smooth muscle layers of the esophageal wall in the aged population. [9][10][11] In addition, underlying disease (such as diabetes mellitus) conditions which is more prevalent in aged people could cause decrease of esophageal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were performed the 10 swallows comprising 5-mL water at 20-second intervals in order to estimate the basal and residual LES pressure, amplitude and duration of esophageal body contraction. 12 …”
Section: Conventional Manometrymentioning
confidence: 99%
“…We reported previously that patients with vigorous achalasia had narrower esophageal lumen and shorter transit times than those of classic achalasia group [24]. The relationship between TBE findings and subtypes defined by HRM has not been clearly elucidated [3,20,25,26]. Another paper also reported that the esophageal width of type I and II achalasia patients was larger than that of type III achalasia, which was consistent with our studies, and the report showed a significant correlation between the barium column height and clinical symptom scores after EPD [25].…”
Section: Discussionmentioning
confidence: 95%